Efficient synthesis of 3,3′-Spirooxindole γ-Butyrolactone via Rongalite-mediated domino reductive aldol and spiro-lactonization reactions - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kinage, Anil K. (ChemistrySelect, 2025)
In this study, we develop a novel methodology involving rongalite-mediated domino reductive/aldol reaction, followed by spiro-lactonization of 2-oxoindolin-3-ylidene acetates/malonates in presence of base to synthesis of 3,3 `-spirooxindole gamma-butyrolactone. The detail study, such as effect of solvent, effect of different base and substrate has been carried out. Scale up of this methodology is also done. Sodium hydroxymethanesulfinate dihydrate (rongalite) concurrently has a dual role in this context; it acts as a reducing agent as well as C1 synthon. This approach offers several advantages, such as being metal- and catalyst-free, involving a simple reaction protocol, having a wide substrate scope, using water as a green solvent, and providing good to excellent yields of the products under mild reaction conditions.
Keywords: (+/-) Coixspirolactam A & [3; 3 `-spirooxindole gamma-butyrolactone]; Domino reductive/aldol/spiro-lactonization; Good step economy; Rongalite as reductant & C1 synthon; Water as a green solvent